Pengaruh Pengalaman Kerja, Pelatihan Dan Prestasi Kerja Terhadap Pengembangan Karir Karyawan Badan Kepegawaian Daerah Provinsi NTB - Ni Luh Putu Widyani Puspitawati; Mukmin Suryatni; I Nyoman Nugraha Ardana Putra (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Employee career development plays an important role for employees, a clear career path is needed by employees. This study aims to determine the effect of work experience, training, work performance on the career development of BKD employees in NTB Province. The research population consisted of all BKD employees in the NTB Province, consisting of 91 respondents. In this study using multiple regression analysis techniques. This type of research is associative research. Data processing in this study uses SPSS 26 For Windows. Based on the research that has been done, it is found that work experience, training and work performance have a positive and significant influence on the career development of BKD employees in NTB Provinci.